Tindak Tutur Persuasif Oleh Tokoh Arataka Reigen Dalam Anime Mob Psychoo 100 - Hidayat, Alfi Nurul; Aibonotika, Arza; Widiati, Sri Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research was conducted to understand how persuasive speechacts are used in daily life. The type of research uused in qualitative descriptive. Thedata source fot this research is the character Arataka Reigen in the anime ‘MobPsychoo 100’ in convicing his costumers. The analysis in this research uses Robert B.Cialdini’s theory on persuasive principles, namelyReciprocity, Commitmen andConsistency, Sosial Proof, Authority, Liking, and Scarity. The data collection methodsuuesd are observation, listeing, and note-taking. The result of this research show 11data points of persuasive speech acts by the character Arataka Reigen with hiscostumers.Keywords: anime, persuasive speech acts, persuasive principles